Extraction and characterization of novel fibers from Vernonia elaeagnifolia as a potential textile fiber - Shaker, Khubab; Waseem Ullah Khan, Raja Muhammad; Jabbar, Madeha; Umair, Muhammad; Tariq, Asra; Kashif, Muhammad; Nawab, Yasir (Industrial crops and products, 2020)
•Biological retting of Vernonia elaeagnifolia creeper plant for extraction of fibers.•Fibre length ranges to 2000 mm or even high.•Tenacity and modulus comparable to jute and cotton.•A potential reinforcement for polymeric composite materials. Vernonia elaeagnifolia plant is primarily used for the wall ornamentations and is abundantly available in countries like Pakistan, India, Burma, etc. The aim of this study is to investigate the use of Vernonia elaeagnifolia as a potential source of natural fibers for the first time and to compare the performance properties with conventional textile fibers. The fibers were extracted from the Vernonia elaeagnifolia plant by biological retting process, which is a green route for the extraction of natural fibers. The material functional groups were studied by the Fourier Transform Infrared spectroscopy. The morphology of extracted fibers was investigated using scanning electron microscopy, the thermal behavior through thermogravimetric analyses and mechanical behavior was tested using single fiber tensile tester (tenacity 16.30 cN/Tex). The volume density of fibers was measured by means of microscopic analysis and its weight (found to be 1.30 g/cm3). The moisture regain of the fibers was evaluated by the oven-dry method to be 9.22%. The performance properties of these fibers are comparable with conventional fibers. They may be used as a reinforcement in polymeric composite materials as they are mechanically as well as thermally stable.